Analysis of extracorporeal photopheresis within the frame of the WAA register. (October 2021) - Blaha, M.; Gasova, Z.; Berlin, G.; Audzijoniene, J.; Griskevicius, A.; Dykes, J.; Bhuiyanova, Z.; Lanska, M.; Eich, T.; Vrielink, H.; Witt, V.; Seval, G.C.; et al.
Abstract: The aim of the study was to investigate safety and if extracorporeal photopheresis (ECP) may change health criteria (HC) and quality of life (QoL). Material and method: 560 patients (33 % women) were treated with ECP for a total of 13, 871 procedures during a 17-years period. Mean age was 48 years (±18, range 3−81 years). Self-estimation of QoL was graded: 0 (suicidal) up to 10 (best ever) and HC: 0 (Bed ridden, ICU condition) up to 10 (athletic). Adverse events were analyzed. ANOVA and paired comparisons were performed. Results: Patients were treated due to graft versus host disease (GVHD, n = 317), skin lymphoma (n = 70), solid organ transplants (n = 47), skin diseases (n = 20) and other diseases (n = 106). Adverse events (AEs) were registered in 5.4 % of the first treatments and in 1.2 % of the subsequent procedures. Severe AEs were present in 0.04 % of all procedures. No patient died due to the procedure. Tingling and stitching were the most common AE. For those with GVHD an improvement was noticed within approximately 10 procedures of ECP in the severity stage, QoL (from a mean of 6.1 to 6.8, p < 0.002) and the HC (6.1 -> 6.4, p < 0.014) and improved further with added procedures. Conclusion: Photopheresis is an established therapy with few side effects. The present study of soft variables indicate that GVHD shows benefits upon ECP within approximately 10 procedures in regard to the severity of mainly skin GVHD, and lower baseline levels of HC and QoL.